1995
DOI: 10.1149/1.2048656
|View full text |Cite
|
Sign up to set email alerts
|

In Situ La, Ce, and Nd L‐Edge X‐Ray Absorption Fine Structure Study of an Intermetallic Metal Hydride Electrode in an Operating Alkaline Battery

Abstract: The x-ray absorption fine structure of a technologically important MmL5 intermetallic compound (Mm = Lao.52Ceo.34Ndo.loPro.o4, L5 = Ni3.sCao.sMno.3AIo.4) in the form of a hydrogen storage cathode was recorded in situ in the region 5440-6290 eV using an electrochemical cell which is essentially a fully functioning alkaline battery. Significant differences were observed in the x-ray absorption near edge structure (XANES) of all of the absorption edges (La, Ce, and Nd) between the uncharged and fully charged s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Techniques to probe the electronic structure at solid/liquid interfaces in situ are, however, still limited. Second harmonic generation (SHG) spectroscopy is one solution to probe the surface electronic structure; however, the spectroscopic SHG study is rather limited, and the interpretation of the results is not straightforward. X-ray absorption near edge structure (XANES) can prove the oxidation state of elements and electronic states at the electrode/electrolyte solution interface . We recently developed an in situ electrochemical X-ray photoelectron spectroscopy (XPS) system combined with a specially designed electrochemical cell with a thin (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques to probe the electronic structure at solid/liquid interfaces in situ are, however, still limited. Second harmonic generation (SHG) spectroscopy is one solution to probe the surface electronic structure; however, the spectroscopic SHG study is rather limited, and the interpretation of the results is not straightforward. X-ray absorption near edge structure (XANES) can prove the oxidation state of elements and electronic states at the electrode/electrolyte solution interface . We recently developed an in situ electrochemical X-ray photoelectron spectroscopy (XPS) system combined with a specially designed electrochemical cell with a thin (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the absorption maxima slightly shift to the lower energy side as the calcination temperature increases (in the inset of Fig.3). This type of phenonmena can be partially attributed to a decrease of the density of empty d-like states near the Fermi level following Nd migration into the silicate lattices Tryk et al, 1995). As noted before, a surplus negative surface charge of octahedral layers is transfered into cationic Nd ions as they are migrated into vacant octahedral sites upon calcination.…”
Section: Resultsmentioning
confidence: 72%
“…Although the electrochemical behavior of Zn anodes in strongly alkaline solutions has received considerable attention both from industrial and academic communities, 1-5 the extent to which the information so far reported may be relevant to an actual operating battery still remains to be determined. Recent efforts in our research group have been aimed at implementing spectroscopic techniques for probing electrodes under conditions which closely mimic those found in real electrochemical devices, 6 in an attempt to avoid such ambiguities. This paper presents a new methodology for the acquisition of in situ Raman spectra of a real Zn anode in a genuine battery environment as a function of time, during high-current discharge.…”
mentioning
confidence: 99%